Lipid Extract of Mycoplasma penetrans Proteinase K-Digested Lipid-Associated Membrane Proteins Rapidly Activates NF-κB and Activator Protein 1 - Feng, Shaw-Huey (American Society for Microbiology, 1999)
Lipid-associated membrane proteins (LAMPs) of Mycoplasma penetrans rapidly induced macrophages to produce proinflammatory cytokines such as tumor necrosis factor alpha (TNF-α). Our analysis showed that the macrophage-stimulating activity of TNF-α production was mainly attributable to a lipid extractable component(s) in the LAMP preparation. Since induction of gene expression is normally preceded by activation of transcriptional factors that bind to their specific recognition elements located in the upstream promoter region, we examined the activity of transcriptional factors, namely, NF-κB and activator protein 1 (AP-1), in thioglycolate exudate peritoneal (TEP) macrophages treated with M. penetrans lipid extract of proteinase K (PK)-digested LAMPs. Initially, in the nuclei of unstimulated TEP cells, there was only a low basal level of active AP-1, and the active form of NF-κB could not be detected. M. penetrans lipid extract of PK-digested LAMPs activated both NF-κB and AP-1 in TEP macrophages within 15 min. The markedly increased activities of both factors gradually declined and dissipated after 2 h. Parallel to the rapid increase of NF-κB and AP-1, the TNF-α transcript also increased significantly 15 min after the stimulation. The high-level expression of TNF-α persisted over 2 h. Dexamethasone blocked the activation of both NF-κB and AP-1 and suppressed the production of TNF-α in TEP macrophages stimulated by M. penetrans lipid extract of PK-digested LAMPs. Our study demonstrates that the M. penetrans lipid extract of PK-digested LAMP is a potent activator for NF-κB and AP-1 in murine TEP macrophages. Our results also suggest that high-level expression of TNF-α in cells induced by M. penetrans lipid extract of PK-digested LAMPs is associated with rapid activation of transcriptional factors NF-κB and AP-1.